2016
DOI: 10.3389/fsurg.2016.00019
|View full text |Cite
|
Sign up to set email alerts
|

Outcome after Surgery of Lumbar Spinal Stenosis: A Randomized Comparison of Bilateral Laminotomy, Trumpet Laminectomy, and Conventional Laminectomy

Abstract: BackgroundLaminectomy is the traditional operating method for the decompression of spinal canal stenosis. New partial decompression processes have been suggested in the treatment of lumbar stenosis. The benefit of a micro surgical approach is the chance of an extensive bilateral decompression of the spinal canal or foramen at one or numerous levels, through a minimal para-spinal muscular separation.PurposeTo match the safety and the clinical consequences after a bilateral laminotomy, laminectomy and trumpet la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 67 publications
2
26
0
Order By: Relevance
“…Finally, a study by Onimus et al in a similar cohort showed that none of their patients (0/16) developed a wound complication when treated with RT 7 days following surgery. 19,20 Our findings echo much of these clinical data and indicate that early RT does not increase the risk of wound complications following resection of a spinal metastasis.…”
Section: Discussionsupporting
confidence: 78%
“…Finally, a study by Onimus et al in a similar cohort showed that none of their patients (0/16) developed a wound complication when treated with RT 7 days following surgery. 19,20 Our findings echo much of these clinical data and indicate that early RT does not increase the risk of wound complications following resection of a spinal metastasis.…”
Section: Discussionsupporting
confidence: 78%
“…Using this data, there is no statistical difference in operative time per level decompressed among the 3 groups. Once the definite learning curve is over and experience has been acquired, the operative time should be shorter than at the beginning of a case series [18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…The results of some studies on clinical consequences in patients with degenerative scoliosis showed the efficiency of minimally invasive decompression specially in isolated lateral listhesis [42][43][44][45].…”
Section: Decompression Onlymentioning
confidence: 99%
“…Recognition and treatment of osteoporosis is essential and may require delaying the surgery 6-18 month while pharmacological intervention is taking place [40,41]. Most common indications for surgery are devastating pain unresponsive to non-operative approaches and severely disturbing the quality of life, neurological disorders, and infrequently cosmetic appearance [40,44,45]. The goal of surgery is the decompression of neural elements by restoration and the maintenance of sagittal and coronal balance [42,46].…”
Section: Surgical Treatmentmentioning
confidence: 99%
See 1 more Smart Citation